1979
DOI: 10.3758/bf03326676
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Richard W. Thompson’s “Comments on Ksir, C. ‘Scopolamine does not reduce tonic immobility in chickens’”

Abstract: Thompson's (1979) comment points out four areas of difficulty in interpreting my results (Ksir, 1978). The first, that strain differences in TI duration might have masked the effects of scopolamine, is a possible explanation of the difference in results between our two studies. However, the saline and methylscopolamine durations reported in my paper were quite similar to the durations reported for their birds under similar drug conditions. Thus, strain differences in scopolamine action, rather than in baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The finding that nicotine produced little or no increase in locomotor activity of rats previously exposed to the test apparatus but not to the drug is compatible with earlier observations (Ksir et al, 1985;1987;Shoaib & Stolerman 1992). Similarly, many studies have shown that previous exposure to nicotine can sensitize rats to its locomotor-activating effect (Clarke & Kumar 1983;Ksir et al, 1985;1987;Shoaib & Stolerman 1992). The results with isoarecolone suggested that rats sensitized to nicotine did not show cross-sensitization to isoarecolone as far as cage crosses, the main measure of locomotion, were concerned (Figure 2a).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that nicotine produced little or no increase in locomotor activity of rats previously exposed to the test apparatus but not to the drug is compatible with earlier observations (Ksir et al, 1985;1987;Shoaib & Stolerman 1992). Similarly, many studies have shown that previous exposure to nicotine can sensitize rats to its locomotor-activating effect (Clarke & Kumar 1983;Ksir et al, 1985;1987;Shoaib & Stolerman 1992). The results with isoarecolone suggested that rats sensitized to nicotine did not show cross-sensitization to isoarecolone as far as cage crosses, the main measure of locomotion, were concerned (Figure 2a).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that the locomotor activating effect of nicotine becomes more marked upon repeated administration of the drug (Clarke & Kumar, 1983;Ksir et al, 1985;1987). Similarly, the locomotor stimulant effect of amphetamine, which is also mediated through increases in extracellular dopamine in the accumbens, can show sensitization after amphetamine is administered repeatedly (Robinson & Becker, 1986).…”
Section: Introductionmentioning
confidence: 99%